Spatially Resolved High Voltage Kelvin Probe Force Microscopy: A Novel Avenue for Examining Electrical Phenomena at Nanoscale - McCluskey, Conor J.; Sharma, Niyorjyoti; Maguire, Jesi R.; Pauly, Serene; Rogers, Andrew; Lindsay, TJ; Holsgrove, Kristina M.; Rodriguez, Brian J.; Soin, Navneet; Gregg, John Marty; McQuaid, Raymond G. P.; Kumar, Amit (Advanced Physics Research, 2024)
Kelvin probe force microscopy (KPFM) is a well‐established scanning probe technique, used to measure surface potential accurately; it has found extensive use in the study of a range of materials phenomena. In its conventional form, KPFM frustratingly precludes imaging samples or scenarios where large surface potential or surface potential gradients exist outside the typical ±10 V window. If the potential regime measurable via KPFM can be expanded, to enable precise and reliable metrology, through a high voltage KPFM (HV‐KPFM) adaptation, it can open up pathways toward a range of novel experiments, where the detection limit of regular KPFM has so far prevented the use of the technique. In this work, HV‐KPFM is realized and shown to be capable of measuring large surface potential and potential gradients with accuracy and precision. The technique is employed to study a range of materials (positive temperature coefficient of resistivity ceramics, charge storage fluoropolymers, and pyroelectrics) where accurate, spatially resolved mapping of surface potential within high voltage regime facilitates novel physical insight. The results demonstrate that HV‐KPFM can be used as an effective tool to fill in existing gaps in surface potential measurements while also opening routes for novel studies in materials physics. High voltage Kelvin probe force microscopy is realized and shown to be capable of measuring large surface potential and potential gradients with accuracy and precision. The technique is employed to study a range of materials where spatially resolved mapping of surface potential within high voltage regime facilitates novel physical insight, thus opening routes for novel studies in materials physics.